Prognostic Comparison Between Liver Resection and Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma Patients With Bile Duct Tumor Thrombus: A Propensity-Score Matching Analysis - Liu, Zong-Han; Sun, Ju-Xian; Feng, Jin-Kai; Yang, Shi-Ye; Chen, Zhen-Hua; Liu, Chang; Chai, Zong-Tao; Mao, Fei-Fei; Guo, Wei-Xing; Shi, Jie; Cheng, Shu-Qun (Frontiers in Oncology, 2022)
Background Hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT) is rare. The aim of this study is to evaluate the long-term prognosis of liver resection (LR) versus transcatheter arterial chemoembolization (TACE) in these patients. Methods Data from HCC patients with BDTT who underwent liver resection and TACE were analyzed respectively. Propensity score matching (PSM) analysis was performed in these patients. Results A total of 145 HCC patients with BDTT were divided into two groups: the LR group (n = 105) and the TACE group (n = 40). The median OS in the LR group was 8.0 months longer than that in the TACE group before PSM (21.0 vs. 13.0 months, P <0.001) and 9.0 months longer after PSM (20.0 vs. 11.0 months, P <0.001). The median DFS in the LR group was 3.5 months longer than that in the TACE group before PSM (7.0 vs. 3.5 months, P = 0.007) and 5 months longer after PSM (7.0 vs. 2.0 months, P = 0.007). Conclusion If surgery is technically feasible, liver resection provides better prognosis for HCC patients with BDTT compared with TACE.